Mismatched Expectations and Perceptions in Undergraduate Thesis Supervision - Sunggingwati, Dyah; Setyowati, Dea Rini; Hermagustiana, Istanti (TLEMC (Teaching and Learning English in Multicultural Contexts), 2024)
Thesis supervision involves both supervisors and supervisees that have different perceptions and expectations. This study aims to explore the perceptions of supervisors and expectations of supervisees. An exploratory case study design was applied in this study. Eleven of 24 supervisors who participated in this study responded to questions about their supervisory given via Google Form. Nine English undergraduate students who are currently working on their undergraduate thesis were involved. A set of questions was distributed to supervisors and semi-structured interview was applied to supervisees. The data were analyzed thematically. The findings revealed that there are mismatched expectations and perceptions that contribute to the complexity of thesis supervision. The supervisors have a positive perception about their relationship with the supervisees. They recognize their supervisees' needs and have professional relationships with their supervisees. They provide help and guidance, such as providing online links of material to support the supervisee’s thesis. Furthermore, they expect their supervisees to have autonomy in learning for their own thesis, have adequate research knowledge and skills, and have good communication skills. However, the supervisees expected that their supervisors recognized each supervisee's characters, needs, and weaknesses. They expect to receive clear and structured instructions to outline their research schedules and activities and to receive oral specific feedback on specific parts of their thesis. This study highlights a need for clarity about the expectations of each party to minimize mismatched expectations.Keywords: thesis expectations, thesis perceptions, undergraduate thesis supervision